Competitive performance prediction of elite alpine skiers - Nilsson, R. (Umeå University, 2019)
Introduction: The overall aim of this doctoral thesis was to identify physiological and anthropometric variables valid for prediction of competitive performance in alpine skiing (indicated by FIS points).